您当前的位置: 首页 > 网页快照
Interferenceless and motionless method for recording digital holograms of coherently illuminated 3D objects by coded aperture correlation holography system
Equations (9). Equations on this page are rendered with MathJax. Learn more. (1) H O B J ( r ¯ ) = ∫ I O B J ( r ¯ , z ) ∗ t ( r ¯ , z ) d z , (2) I I M G ( r ¯ , z j ) = H O B J ( r ¯ ) ⊗ R ( r ¯ , z j ) , (3) A I n ( r ¯ ) ∗ f ( r ¯ ) 2 ≈ A I n ( r ¯ ) 2 ∗ q ( r ¯ ) , (4) A I n ( r ¯ ) ∗ ∑ k a k δ ( r ¯ − r ¯ k ) 2 = ∑ k a k A I n ( r ¯ − r ¯ k ) 2 = ∑ k a k 2 A I n ( r ¯ − r ¯ k ) 2 = A I n ( r ¯ ) 2 ∗ ∑ k a k 2 δ ( r ¯ − r ¯ k ) , (5) I k = O ( r ¯ R / r ¯ R M T M T ) 2 ∗ ∑ i = 1 N a i 2 δ ( r ¯ R − r ¯ k , i ) , (6) I I M G = H O B J ⊗ H P S H ′ = O ( r ¯ R / r ¯ R M T M T ) ∗ H P S F 2 ⊗ H P S H ′ = O ( r ¯ R / r ¯ R M T M T ) ∗ [ ∑ i = 1 N a i δ ( r ¯ R − r ¯ 1 , i ) − ∑ i = 1 N b i δ ( r ¯ R − r ¯ 2 , i ) ] 2 ⊗ H P S H ′ = O ( r ¯ R / r ¯ R M T M T ) 2 ∗ [ ∑ i = 1 N a i 2 δ ( r ¯ R − r ¯ 1 , i ) − ∑ i = 1 N b i 2 δ ( r ¯ R − r ¯ 2 , i ) ] ⊗ H P S H ′ = F − 1 { F [ O ( r ¯ R / r ¯ R M T M T ) 2 ] F [ ∑ i = 1 N a i 2 δ ( r ¯ R − r ¯ 1 , i ) − ∑ i = 1 N b i 2 δ ( r ¯ R − r ¯ 2 , i ) ] exp ⁡ ( − j φ ) } = F − 1 { F [ O ( r ¯ R / r ¯ R M T M T ) 2 ] h exp ⁡ ( j φ ) exp ⁡ ( − j φ ) } = O ( r ¯ R / r ¯ R M T M T ) 2 ∗ F − 1 { h } ≈ O ( r ¯ R / r ¯ R M T M T ) 2 , (7) F { ∑ i = 1 N a i 2 δ ( r ¯ R − r ¯ 1 , i ) − ∑ i = 1 N b i 2 δ ( r ¯ R − r ¯ 2 , i ) } = h exp ⁡ ( j φ ) . (8) H O B J = ∑ q = 1 P { O q ( r ¯ R / r ¯ R M T M T ) 2 ∗ ∑ p = 1 P [ ∑ i = 1 N a p , i g q , p ( r ¯ R − r ¯ 1 , p , i ) − ∑ i = 1 N b p , i g q , p ( r ¯ R − r ¯ 2 , p , i ) ] } , (9) I I M G = H O B J ⊗ H P S H , l ′ = ∑ q = 1 P { O q ( r ¯ R / r ¯ R M T M T ) 2 ∗ ∑ p = 1 P [ ∑ i = 1 N a p , i g q , p ( r ¯ R − r ¯ 1 , p , i ) − ∑ i = 1 N b p , i g q , p ( r ¯ R − r ¯ 2 , p , i ) ] } ⊗ H P S H , l ′ = ∑ q = 1 P O q ( r ¯ R / r ¯ R M T M T ) 2 ∗ [ ∑ i = 1 N a q , i δ ( r ¯ R − r ¯ 1 , q , i ) − ∑ i = 1 N b q , i δ ( r ¯ R − r ¯ 2 , q , i ) ] ⊗ H P S H , l ′ + ∑ q = 1 P ∑ p ≠ q P O q ( r ¯ R / r ¯ R M T M T ) 2 ∗ [ ∑ i = 1 N a p , i g q , p ( r ¯ R − r ¯ 1 , p , i ) − ∑ i = 1 N b p , i g q , p ( r ¯ R − r ¯ 2 , p , i ) ] ⊗ H P S H , l ′ ≈ O l ( r ¯ R / r ¯ R M T M T ) 2 + ∑ q ≠ l P O q ( r ¯ R / r ¯ R M T M T ) 2 ∗ g q , l ( r ¯ R ) . .
From: